Dynamic transcriptome landscape in the song nucleus HVC between juvenile and adult zebra finches - Zhimin Shi; Zeyu Zhang; Lana Schaffer; Zhi Huang; Lijuan Fu; Steven Head; Terry Gaasterland; Xiu‐Jie Wang; XiaoChing Li (Advanced Genetics, 2021)
Abstract Male juvenile zebra finches learn to sing by imitating songs of adult males early in life. The development of the song control circuit and song learning and maturation are highly intertwined processes, involving gene expression, neurogenesis, circuit formation, synaptic modification, and sensory‐motor learning. To better understand the genetic and genomic mechanisms underlying these events, we used RNA‐Seq to examine genome‐wide transcriptomes in the song control nucleus HVC of male juvenile (45 d) and adult (100 d) zebra finches. We report that gene groups related to axon guidance, RNA processing, lipid metabolism, and mitochondrial functions show enriched expression in juvenile HVC compared to the rest of the brain. As juveniles mature into adulthood, massive gene expression changes occur. Expression of genes related to amino acid metabolism, cell cycle, and mitochondrial function is reduced, accompanied by increased and enriched expression of genes with synaptic functions, including genes related to G‐protein signaling, neurotransmitter receptors, transport of small molecules, and potassium channels. Unexpectedly, a group of genes with immune system functions is also developmentally regulated, suggesting potential roles in the development and functions of HVC. These data will serve as a rich resource for investigations into the development and function of a neural circuit that controls vocal behavior.